Patient, physician, and policy factors underlying variation in use of telemedicine for radiation oncology cancer care. (16th March 2022) - De, Brian; Fu, Shuangshuang; Chen, Ying‐Shiuan; Das, Prajnan; Ku, Kimberly; Maroongroge, Sean; Woodhouse, Kristina D.; Hoffman, Karen E.; Nguyen, Quynh‐Nhu; Reed, Valerie K.; Chen, Aileen B.; Koong, Albert C.; et al.
Abstract: Background: Oncology telemedicine was implemented rapidly after COVID‐19. We examined multilevel correlates and outcomes of telemedicine use for patients undergoing radiotherapy (RT) for cancer. Methods: Upon implementation of a telemedicine platform at a comprehensive cancer center, we analyzed 468 consecutive patient RT courses from March 16, 2020 to June 1, 2020. Patients were categorized as using telemedicine during ≥1 weekly oncologist visits versus in‐person oncologist management only. Temporal trends were evaluated with Cochran‐Armitage tests; chi‐squared test and multilevel multivariable logistic models identified correlates of use and outcomes. Results: Overall, 33% used telemedicine versus 67% in‐person only oncologist management. Temporal trends ( p trend < 0.001) correlated with policy changes: uptake was rapid after local social‐distancing restrictions, reaching peak use (35% of visits) within 4 weeks of implementation. Use declined to 15% after national "Opening Up America Again" guidelines. In the multilevel model, patients more likely to use telemedicine were White non‐Hispanic versus Black or Hispanic (odds ratio [OR] = 2.20, 95% confidence interval [CI] 1.03–4.72; p = 0.04) or receiving ≥6 fractions of RT versus 1–5 fractions (OR = 4.49, 95% CI 2.29–8.80; p < 0.001). Model intraclass correlation coefficient demonstrated 43% utilization variation was physician‐level driven. Treatment toxicities and 30‐day emergency visits or unplanned hospitalizations did not differ for patients using versus not using telemedicine ( p > 0.05, all comparisons). Conclusion: Though toxicities were similar with telemedicine oncology management, there remained lower uptake among non‐White patients. Continuing strategies for oncology telemedicine implementation should address multilevel patient, physician, and policy factors to optimize telemedicine's potential to surmount—and not exacerbate—barriers to quality cancer care. Abstract : In this analysis of 468 consecutive patients undergoing radiotherapy after the COVID‐19 pandemic‐driven implementation of an audiovisual telemedicine platform at a large comprehensive cancer center, non‐White patients were less likely to use telemedicine during acute cancer treatment, and 43% of the variation in use patterns was physician‐driven. The risk of treatment toxicities and 30‐day emergency visits or unplanned hospitalizations did not differ by use vs. no use of telemedicine.